Some Legal Aspects of Plagiarism Among Students - Sokołowska, Anna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
The paper describes the scope of the legal consequences of plagiarism among students in terms of copyright. The main question is connected with the scope and nature of the copyright protection against plagiarism. The issue is related to the specificity of the social role played by a student and to certain customs in the university community which enforce a certain behaviour and do not always require detailed references to the sources used. All university students have administrative and legal liabilities with regard to the university authorities, and in addition they bear full civil liability for their actions